ENTERPRISE RESOURCE PLANNING SCORECARDS AND MANAGERIAL PERFORMANCE - Mansor, Noorhayati; Bahar, Asniati (Jurnal Akuntansi dan Governance Andalas, 2015)
Shang and Seddon (2002) present a framework for assessing the business benefits of Enterprise Resource Planning (ERP) systems. Chand et al. (2005) contributes to the study of ERP benefits by incorporating the balanced scorecard (BSC) framework. The BSC has been reported to improved the quality of decisions (Valiris, Chytas, and Glykas, 2005; Bremser and Chung, 2005) and enables managers to make a comprehensive assessment of companies operations (Kaplan and Norton, 1993). Existing work on the combined ERP system and BSC includes Rosemann and Wiese (1999), Wier, et al., (2007) and Mansor and Bahari, (2008). An ERP Scorecard was introduced by Chand et. al. (2005) to evaluate the ERP benefits at different managerial levels. However, their findings are subject to the limitations of case study methodology. The present paper extends the work of Chand et al. (2005) and proposes an empirical study to evaluate the perceived ERP benefits at the operational, tactical and strategic levels. A mix methodology is adopted. The first stage involves semi-structured personal interviews of CEOs to develop a set of questionnaire. In the second stage, managers of Malaysian manufacturing companies are randomly selected to respond to the structured questionnaire. The main objective of the study is to determine the relationship (if any) between ERP benefits and decision levels. The findings of this research are expected to improve the designs, applications and effectiveness of performance management system in the strategic information system environment.